Implikasi Pernikahan Dini bagi Generasi Muda Era Milenial - Teni Marzela; Nyayu Siti Fatimah; Lathifah Lathifah; Dwi Noviani (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This article aims to explain in more depth that early marriage is taking away the nation's future. Early marriage in Indonesia is an increasing trend. This is demonstrated by data revealing high numbers of requests for marriage dispensation in the Religious Courts in a number of regions. In fact, sadly, the high number of requests for marriage dispensation, according to data from the National Population and Family Planning Agency (BKKBN), 80% of them are due to pregnancy out of wedlock. Marriage is an important thing in the human life cycle. One of the reasons for marrying young is to avoid promiscuity that violates religious and social norms, as well as reducing the burden on parents. Early marriage is a phenomenon that robs the nation of its future. This article discusses the negative impact of early marriage on children's growth, society, education and public health. By analyzing the factors that influence the continuation of early marriage, it is hoped that effective preventive steps can be taken to protect the future of future generations.